A heterostructure composite material for lithium ion batteries and a preparation method thereof

CN122950426APending Publication Date: 2026-10-20CHENGDU UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611016196.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-09
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0004]然而,现有技术中的异质结构复合材料仍存在诸多缺陷:一方面,异质结构的组分比例往往难以精确控制,当比例失衡时,内建电场效应不足,无法有效降低电荷转移阻抗;另一方面,单纯的异质结构在长时间循环中仍难以克服纳米颗粒的团聚及体积应变问题;此外,现有制备工艺通常较为繁琐,且难以在实现组分精确调控的同时获得具有特定微观形貌及原位碳包覆的均匀复合材料

Benefits of technology

本发明提出一种用于锂离子电池的异质结构复合材料及其制备方法,通过构建包含金属氧化物相、金属硫化物相及原位碳相的二维纳米片异质结构复合材料,有效解决了现有技术中金属氧化物负极材料导电性差、循环过程中体积变化大的技术问题。具体而言,基于金属有机框架前驱体衍生而来的原位碳相,不仅均匀包覆于异质结构纳米晶体表面,构成导电网络并提升了整体电子导电性,还作为物理缓冲层适应了充放电过程中的体积应变,有效防止了纳米颗粒的团聚和结构坍塌;同时,二维纳米片状形貌缩短了电子与锂离子的传输距离,而异质结构界面处诱导产生的内建电场则显著降低了界面电荷转移阻抗,促进了电化学反应动力学性能,大幅降低了电极极化现象(例如过电位可显著降低至0.06V),从而实现了优异的倍率性能和循环稳定性;此外,本发明还通过简单的硫化时间控制,实现了材料中金属氧化物与金属硫化物组分比例的精确调控,确保了复合材料始终处于最优电化学性能区间。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses a heterostructure composite material for lithium-ion batteries and its preparation method. The composite material uses a two-dimensional Zn-BTC metal-organic framework as a precursor, and achieves partial sulfidation and organic ligand carbonization through in-situ thermal annealing with thioacetamide to construct ZnO / ZnS@C heterostructure nanosheets, which are then loaded onto reduced graphene oxide (rGO). By controlling the S / Zn molar ratio through sulfidation time, the resulting material is assembled from nanoparticles with a particle size of less than 5 nm into a porous structure, with an in-situ carbon layer coating the surface. This invention utilizes the synergistic effect of the built-in electric field of the heterostructure and the conductive substrate of rGO to effectively reduce charge transfer impedance and electrochemical overpotential, endowing the composite material with excellent rate performance (discharge capacity greater than 265 mAh / g at 5C current density) and long-term cycle stability (capacity retention greater than 67% after 100 cycles at 0.5C), making it suitable for high-performance lithium-ion battery applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of new energy storage materials technology, specifically relating to a heterostructure composite material for lithium-ion batteries and its preparation method. Background Technology

[0002] Lithium-ion batteries, due to their high energy density, long cycle life, and environmental friendliness, have become the primary energy storage devices in electric vehicles and portable electronic devices. To meet the ever-increasing demand for high energy density, researchers are dedicated to developing novel high-capacity anode materials to replace traditional commercial graphite anodes (with a theoretical specific capacity of only 372 mAh / g). Among these, transition metal oxides (such as zinc oxide) are considered highly promising candidate materials due to their high theoretical specific capacity of up to 987 mAh / g and low cost. However, the inherent poor conductivity of metal oxides and the dramatic volume expansion and contraction during charge-discharge cycles directly lead to pulverization of the electrode material structure and rapid degradation of electrochemical performance, severely restricting their commercial application.

[0003] To address these issues, existing technologies typically employ strategies such as nanostructure design, compositing with conductive carbon materials, and constructing heterostructures. For example, constructing a heterostructure by compositing zinc oxide with zinc sulfide can improve conductivity and reaction kinetics by utilizing charge redistribution and built-in electric field effects at the heterostructure interface.

[0004] However, existing heterostructure composite materials still have many drawbacks: on the one hand, the component ratio of heterostructures is often difficult to control precisely, and when the ratio is unbalanced, the built-in electric field effect is insufficient and cannot effectively reduce charge transfer impedance; on the other hand, simple heterostructures still cannot overcome the problems of nanoparticle aggregation and volume strain during long-term cycling; in addition, existing preparation processes are usually cumbersome and it is difficult to obtain uniform composite materials with specific microstructures and in-situ carbon coating while achieving precise control of components.

[0005] Therefore, how to construct a transition metal oxide / sulfide heterostructure anode material with precise controllable composition, stable structure, and excellent electrochemical performance (especially high rate performance and long cycle stability) through a simple and efficient process remains a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0006] The purpose of this invention is to overcome the shortcomings of the prior art and provide a heterostructure composite material for lithium-ion batteries and its preparation method.

[0007] To achieve the above objectives, the present invention provides the following technical solution: This application provides a heterostructured composite material for lithium-ion batteries, comprising a metal oxide phase, a metal sulfide phase, and an in-situ carbon phase; The metal oxide phase and the metal sulfide phase form a heterostructure, and the composite material exhibits a two-dimensional nanosheet morphology.

[0008] Preferably, the molar ratio R of sulfur to zinc in the composite material satisfies the following formula: R = n(S) / n(Zn) Wherein, n(S) is the amount of sulfur in the composite material, n(Zn) is the amount of zinc in the composite material, and 0.56≤R≤0.81.

[0009] A method for preparing the above-described heterostructure composite material includes: thermally annealing a metal-organic framework precursor and a sulfur source under an inert atmosphere. The temperature T and heating rate v of the heat annealing process satisfy: T = 500℃, v = 2℃ / min.

[0010] Preferably, the metal-organic framework precursor is a two-dimensional zinc-1,3,5-benzenetricarboxylic acid (Zn-BTC) nanosheet, and the sulfur source is thioacetamide (TAA). The ratio of the mass m(TAA) of the sulfur source to the mass m(Zn-BTC) of the metal-organic framework precursor satisfies: m(TAA):m(Zn-BTC)=150:68.

[0011] Preferably, prior to the thermal annealing treatment, the method further includes a step of mixing graphene oxide with the metal-organic framework precursor; The ratio of the mass m(GO) of the graphene oxide to the mass m(Zn-BTC) of the metal-organic framework precursor satisfies: (GO):m(Zn-BTC)=5:3.

[0012] Preferably, the composite material has a porous structure, with a BET specific surface area S_BET and a pore volume V. pore Satisfy S BET =126.39m² / g, V pore =0.41cm³ / g.

[0013] Preferably, the composite material is assembled from nanoparticles, and the grain size d of the nanoparticles satisfies: d≤5nm.

[0014] Preferably, the in-situ carbon phase coats the surface of the metal oxide phase and the metal sulfide phase, and the overpotential η of the composite material when used as a negative electrode of a lithium-ion battery satisfies η≤0.06V.

[0015] Preferably, under a discharge rate of 0.1C, the discharge capacity C of the composite material is... discharge Satisfy: Cdischarge ≥1044mAh / g.

[0016] Preferably, the composite material further includes a reduced graphene oxide substrate, and the two-dimensional nanosheet-shaped composite material is loaded on the reduced graphene oxide substrate; The discharge capacity C of the composite material at a rate of 5C 5C Satisfy: C 5C ≥265mAh / g; and the capacity retention rate CR of the composite material after 100 charge-discharge cycles at a current density of 0.5C satisfies the following formula: CR=(C 100 / C2)×100% Among them, C 100 C1 represents the discharge capacity of the 100th cycle, C2 represents the discharge capacity of the 2nd cycle, and CR ≥ 67%.

[0017] Compared with the prior art, this application has the following beneficial effects: This invention proposes a heterostructure composite material for lithium-ion batteries and its preparation method. By constructing a two-dimensional nanosheet heterostructure composite material containing a metal oxide phase, a metal sulfide phase, and an in-situ carbon phase, it effectively solves the technical problems of poor conductivity and large volume change during cycling of metal oxide anode materials in the prior art. Specifically, the in-situ carbon phase derived from the metal-organic framework precursor not only uniformly coats the surface of the heterostructure nanocrystals, forming a conductive network and improving overall electronic conductivity, but also acts as a physical buffer layer to adapt to volumetric strain during charging and discharging, effectively preventing nanoparticle aggregation and structural collapse. Simultaneously, the two-dimensional nanosheet morphology shortens the electron-lithium ion transport distance, while the built-in electric field induced at the heterostructure interface significantly reduces interfacial charge transfer impedance, promotes electrochemical reaction kinetics, and greatly reduces electrode polarization (e.g., overpotential can be significantly reduced to 0.06V), thereby achieving excellent rate performance and cycle stability. Furthermore, this invention achieves precise control of the ratio of metal oxides to metal sulfides in the material through simple sulfidation time control, ensuring that the composite material is always within the optimal electrochemical performance range. Attached Figure Description

[0018] Figure 1 This is a schematic diagram of the preparation process of zinc oxide / zinc sulfide@C composite material in an embodiment of the present invention.

[0019] Figure 2 The X-ray diffraction (XRD) spectra of zinc oxide / zinc sulfide@C (including 2H, 4H and 6H) composite materials prepared at different sulfidation times in the embodiments of the present invention are shown.

[0020] Figure 3 The images shown are X-ray photoelectron spectroscopy (XPS) spectra of the zinc oxide / zinc sulfide@C-4H composite material in the embodiments of the present invention; wherein, (a) is a full scan spectrum, (b) is a high-resolution XPS spectrum of Zn2p, (c) is a high-resolution XPS spectrum of C1s, (d) is a high-resolution XPS spectrum of O1s, and (e) is a high-resolution XPS spectrum of S2p.

[0021] Figure 4 These are scanning electron microscope (SEM) images of the Zn-BTC precursor and the zinc oxide / zinc sulfide@C-4H composite material in the embodiments of the present invention; wherein, (a) to (c) are SEM images of the Zn-BTC precursor at different magnifications, and (d) to (f) are SEM images of the zinc oxide / zinc sulfide@C-4H composite material at different magnifications.

[0022] Figure 5 The figures show the morphology and elemental distribution of the zinc oxide / zinc sulfide@C-4H composite material in the embodiments of the present invention; wherein, (a) is a SEM image, (b) is the corresponding EDS spectrum, and (c) to (f) are the distribution diagrams of C, O, Zn and S elements, respectively.

[0023] Figure 6 These are transmission electron microscope (TEM) images of the zinc oxide / zinc sulfide@C-4H composite material in the embodiments of the present invention; wherein, (a) and (b) are TEM images at different magnifications, (c) is a high-resolution transmission electron microscope (HRTEM) image, and (d) is the corresponding selected area electron diffraction (SAED) pattern.

[0024] Figure 7 Figure 1 shows the nitrogen adsorption-desorption characterization of the zinc oxide / zinc sulfide@C-4H composite material in the embodiments of the present invention; wherein, (a) is the nitrogen adsorption-desorption isotherm, and (b) is the corresponding pore size distribution curve.

[0025] Figure 8 This is a thermogravimetric analysis (TGA) curve of the zinc oxide / zinc sulfide@C-4H composite material in an air atmosphere in an embodiment of the present invention.

[0026] Figure 9 The figures show a comparison of battery performance between the composite materials prepared at different sulfidation times and commercial zinc oxide in the embodiments of the present invention; wherein, (a) is a rate performance diagram at different current densities, and (b) is a cycle stability diagram at a current density of 0.5C.

[0027] Figure 10The figures show the electrochemical impedance spectroscopy (EIS) spectra of zinc oxide / zinc sulfide@C-2H, 4H and 6H composite materials before and after 100 charge-discharge cycles in the embodiments of the present invention; wherein, (a) is the Nyquist plot, (b) is the equivalent circuit diagram used for EIS spectrum fitting, and (c) is the corresponding histogram of fitted resistance values.

[0028] Figure 11 Figure 1 shows the electrochemical performance of the zinc oxide / zinc sulfide@C-4H composite electrode in the embodiments of the present invention; wherein, (a) is the cyclic voltammetry (CV) curve of the first 5 cycles at a scan rate of 0.2 mV / s, and (b) is the charge-discharge curve of the first 5 cycles at a rate of 0.1 C.

[0029] Figure 12 The figures show a comparison of the electrochemical performance of zinc oxide / zinc sulfide@C and zinc oxide / zinc sulfide@C@rGO composite electrodes in the embodiments of the present invention; wherein, (a) is the rate performance graph, (b) is the cycle performance graph at 0.5C, (c) is the charge-discharge curve graph corresponding to different rates, and (d) is the charge-discharge curve graph corresponding to the 1st, 50th and 100th cycles at 0.5C.

[0030] Figure 13 The figures show the differential capacity (dQ / dV) curves of the zinc oxide / zinc sulfide@C and zinc oxide / zinc sulfide@C@rGO composite electrodes in the embodiments of the present invention; wherein, (a) is the dQ / dV curve of the zinc oxide / zinc sulfide@C electrode for the first 5 cycles at 0.1C, and (b) is the dQ / dV curve of the zinc oxide / zinc sulfide@C@rGO electrode for the first 5 cycles at 0.1C.

[0031] Figure 14 The figures show a comparison of the electrochemical performance of zinc oxide@C@rGO and zinc oxide / zinc sulfide@C@rGO composite electrodes in the comparative examples and embodiments of the present invention; wherein, (a) is the rate performance figure and (b) is the cycle performance figure at 0.5C.

[0032] Figure 15 The figures show the electrochemical impedance spectroscopy and diffusion kinetics analysis of zinc oxide / zinc sulfide@C@rGO and zinc oxide@C@rGO composite materials in the embodiments and comparative examples of this invention; wherein, (a) is the EIS spectrum and equivalent circuit fitting curve before cycling, (b) is the EIS spectrum after 100 cycles, and (c) is the low-frequency region Z' and angular frequency (ω) of the two composite materials before and after cycling. - A linear relationship graph between ¹ / ²). Detailed Implementation

[0033] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0034] Furthermore, in this invention, an element referred to as fixed to or disposed on another element may be directly disposed on the other element, or there may be an intermediate element. When an element is considered to be connected to another element, it may be directly connected to the other element, or there may be an intermediate element present simultaneously. The terms vertical, horizontal, left, right, and similar expressions used herein are for illustrative purposes only and do not represent the only possible implementation.

[0035] Example 1 This embodiment illustrates the preparation of metal-organic framework precursors (Zn-BTC nanosheets): This embodiment provides a method for preparing two-dimensional metal-organic framework precursor nanosheets. The specific steps are as follows: 2 mol of zinc oxide powder and 0.4 mol of 1,3,5-benzenetricarboxylic acid were added to a mixed solvent of 30 mL of deionized water and 30 mL of ethanol, and the reaction vessel volume was 100 mL. The reaction vessel was then transferred to an ultrasonic cleaner and subjected to continuous ultrasonic treatment at a working frequency of 40 kHz and a power of 99% for 4 hours. After the reaction, the resulting white suspension was centrifuged at 8000 rpm to collect the precipitate, which was then washed three times with deionized water and anhydrous ethanol, respectively. Finally, the precipitate was dried in a vacuum oven at 60 °C for 8 hours to obtain the Zn-BTC nanosheet precursor, which exhibited a typical two-dimensional plate-like morphology with a lateral size in the micrometer range.

[0036] Example 2 This embodiment, based on the aforementioned embodiments, illustrates the preparation and vulcanization time control of heterostructured composite materials (ZnO / ZnS@C): This embodiment provides a method for preparing a metal oxide / sulfide heterostructure composite material based on the above-mentioned precursor, and investigates the effect of sulfidation time on the product properties.

[0037] like Figure 1As shown, ZnO / ZnS@C heterostructures were prepared using Zn-BTC nanosheets prepared in Example 1 as precursor materials through partial sulfidation. 68 mg of Zn-BTC precursor was laid flat in a quartz boat, and 150 mg of thioacetamide (TAA) was placed on top of it. Under a nitrogen atmosphere, the temperature was increased to 500 °C at a rate of 2 °C / min, and annealed for 2 hours, 4 hours, and 6 hours respectively to control the degree of sulfidation. During this process, sulfur-containing substances generated by the thermal decomposition of TAA diffused downwards and reacted with the Zn-BTC precursor, while the organic ligands in the Zn-BTC framework underwent in-situ carbonization. Finally, three composite materials with different sulfidation times were obtained, labeled ZnO / ZnS@C-2H, ZnO / ZnS@C-4H, and ZnO / ZnS@C-6H, respectively.

[0038] Example 3 This embodiment, based on the foregoing embodiments, describes the preparation of graphene composite heterostructure material (ZnO / ZnS@C@rGO): To further improve conductivity and structural stability, this embodiment introduces reduced graphene oxide as a conductive substrate.

[0039] First, graphene oxide (GO) and the Zn-BTC precursor prepared in Example 1 were mixed at a mass ratio of 5:3. The mixture was then thoroughly dispersed and homogenized by simple ultrasonic treatment and magnetic stirring, followed by freeze-drying to obtain a GO / Zn-BTC composite precursor. The obtained GO / Zn-BTC composite precursor was uniformly spread on a quartz boat, and TAA was placed on top. The quartz boat was placed in a tube furnace and heated to 500°C at a heating rate of 2°C / min under nitrogen protection, and held at that temperature for 4 hours. During this process, GO was simultaneously reduced to reduced graphene oxide (rGO), while Zn-BTC underwent in-situ carbonization and a sulfidation reaction with the decomposition products of TAA. Finally, a ZnO / ZnS@C nanosheet composite material loaded on an rGO substrate was obtained, labeled as ZnO / ZnS@C@rGO.

[0040] Comparative Example 1 Preparation of sulfur-free composite material (ZnO@C@rGO): In contrast, the same process steps as in Example 3 were used, but thioacetamide (TAA) was not added during the annealing process; that is, GO was simply mixed with the Zn-BTC precursor and annealed at 500°C for 4 hours at a rate of 2°C / min under nitrogen protection; during this process, only the reduction of GO and the carbonization of Zn-BTC occurred, and the product did not contain the zinc sulfide phase, but only had the ZnO@C@rGO structure.

[0041] Comparative Example 2 Acquisition of commercial zinc oxide anode materials: Commercially available zinc oxide nanoparticles were used directly as the active material in the comparative test.

[0042] Test Example 1 This embodiment analyzes the crystal structure and phase composition: like Figure 2 As shown, X-ray diffraction (XRD) analysis was performed on the ZnO / ZnS@C-2H, 4H, and 6H composite materials prepared in Example 2. The results showed that the diffraction peaks of these three composite materials were all attributed to ZnS with a hexagonal wurtzite structure (PDF#36-1450, space group: P63mc(186)) and ZnO with a hexagonal wurtzite structure (PDF#36-1451, space group: P63mc(186)), confirming that ZnO and ZnS coexist and that the heterostructure was successfully constructed.

[0043] Specifically, the peaks at 26.9°, 28.5°, 30.5°, 39.6°, 47.6°, 51.8°, 56.4°, 63.6°, and 72.9° correspond to the (hkl) crystal planes (100), (002), (101), (102), (110), (103), (112), (202), and (203) of ZnS, respectively; while the peaks at 31.8°, 31.4°, 36.3°, and 47.5° correspond to the (hkl) crystal planes (100), (002), (101), (102), (110), (103), (112), (202), and (203). The peaks at 56.0°, 62.8°, 66.4°, 67.9° and 69.1° are attributed to the hexagonal ZnO crystal planes (100), (002), (101), (102), (110), (103), (200), (112) and (201). As the sulfidation time increases from 2h to 6h, the relative diffraction peak intensities of the ZnO phase gradually decrease, indicating that the degree of ZnO to ZnS conversion increases with the increase of sulfidation time.

[0044] Test Example 2 As shown in the table below: The zinc and sulfur content in the composite material of Example 2 was detected by ICP (inductively coupled plasma atomic emission spectrometry). ICP analysis showed that the molar ratio of sulfur to zinc increased with the extension of vulcanization time. When the vulcanization time increased from 2 hours to 4 hours, the S / Zn molar ratio increased from 0.56 to 0.58. When the annealing time was further extended to 6 hours, the S / Zn molar ratio reached 0.81. This result is in high agreement with the changes in peak intensity in the XRD pattern, indicating that the composition of the zinc oxide / zinc sulfide@C composite material can be controlled by the reaction time between TAA and Zn-BTC.

[0045] Test Example 3 X-ray photoelectron spectroscopy (XPS) analysis was performed on the ZnO / ZnS@C-4H sample from Example 2; Figure 3 As shown in a (full scan spectrum), the full spectrum confirms that the material mainly contains Zn, O, C, and S elements; Figure 3 b is the high-resolution spectrum of Zn2p, showing two characteristic peaks at 1021.8 eV and 1044.8 eV, with an interpeak spacing of 23 eV, attributed to Zn2p3 / 2 and Zn2p1 / 2 respectively, indicating that the valence state of zinc is +2; Figure 3 The high-resolution C1s spectrum of c shows that the peak position originates from the decomposition of organic ligands in the Zn-BTC precursor. The peak at 284.5 eV is related to sp² hybridized carbon atoms (C=C), and the peaks at 285.8 eV and 288.2 eV correspond to CO and C=O bonds, respectively, confirming the formation of the in-situ carbon coating. Figure 3 The O1s spectrum of d shows that the peak at 531.1 eV corresponds to O² in the ZnO lattice. - The peaks at 531.8 eV and 532.8 eV are attributed to the anoxic region and oxygen-containing functional groups such as CO. Figure 3 The high-resolution S2p spectrum of e corresponds to S2p3 / 2 and S2p1 / 2 at 161.2 eV and 162.2 eV, respectively, confirming that S² - The characteristic valence states of ZnO, whose intensity ratio is not the standard 2:1, indicate that there are complex chemical interactions between ZnO and sulfur, carbon, and zinc.

[0046] Test Example 4 like Figure 4 As shown, the morphology of the material was observed using a scanning electron microscope (SEM); Figure 4 As shown in a to 4c, the Zn-BTC precursor exhibits a smooth two-dimensional plate-like structure with a lateral dimension of several micrometers and an extremely thin thickness; Figure 4 As shown in d to 4f, after carbonization and sulfidation, the obtained ZnO / ZnS@C-4H completely inherits the two-dimensional nanosheet morphology of the precursor, but the lateral size is slightly reduced and the surface is rough, forming a porous structure composed of tightly assembled nanoparticles.

[0047] like Figure 5 As shown, the EDS spectrum of the ZnO / ZnS@C-4H composite material ( Figure 5 b) and element distribution map ( Figure 5 (cf) further confirmed that the nanosheet is mainly composed of zinc ( Figure 5 e), carbon ( Figure 5 c) Oxygen Figure 5 d) and sulfur ( Figure 5 f) Elemental composition; all elements are uniformly distributed in the composite material, indicating that TAA has been successfully decomposed and the Zn-BTC precursor has completed the sulfidation / carbonization reaction.

[0048] Test Example 5 like Figure 6 As shown, using transmission electron microscopy (TEM) ( Figure 6 a, 6b) and high-resolution transmission electron microscopy (HRTEM) Figure 6 c) The microstructure of ZnO / ZnS@C-4H was characterized in detail; low-magnification TEM ( Figure 6 (a) and (6b) show that the nanosheets are porous and extremely thin, assembled from nanoparticles; HRTEM ( Figure 6 c) Clearly, ZnO and ZnS nanocrystals are closely arranged and embedded in a ligand-derived carbon matrix (confirmed by the amorphous carbon layer encapsulating the crystalline grains), with grain sizes less than about 5 nm. Distinct lattice fringes can be clearly observed: lattice fringes with a spacing of 0.227 nm belong to the (102) crystal plane of ZnS, while lattice fringes with spacings of 0.135 nm and 0.247 nm correspond to the (201) and (101) crystal planes of ZnO, respectively. Figure 6 The selected area electron diffraction (SAED) pattern shown in d contains both the (102) crystal plane of ZnO and the (100) and (103) crystal planes of the ZnS phase, confirming the polycrystalline nature of the heterostructure and its successful construction.

[0049] Test Example 6 The pore structure of ZnO / ZnS@C-4H was characterized using nitrogen adsorption-desorption (BET) testing; for example... Figure 7 As shown in a, the nitrogen adsorption-desorption isotherm is a typical type IV isotherm with a characteristic hysteresis loop; the BET specific surface area of ​​the composite material is 126.39 m² / g, and the pore volume is 0.41 cm³ / g. Figure 7 The pore size distribution curve of b shows that there is a micropore peak at 1.72 nm and a broad mesopore distribution in the range of 2.1 to 100 nm. This micropore-mesopore hierarchical pore structure is conducive to rapid electrolyte wetting and provides abundant electrochemical active sites, while effectively buffering mechanical stress during the charging and discharging process.

[0050] Test Example 7 To quantitatively determine the carbon content of the composite material, a thermogravimetric analysis (TGA) was performed on ZnO / ZnS@C-4H at a heating rate of 10 °C / min in air. Figure 8 The results showed that there was a mass loss of about 14.2 wt% between 400 °C and 650 °C, which corresponds entirely to the combustion of the carbon components generated after the in-situ carbonization of the organic ligands in the Zn-BTC precursor in air.

[0051] Test Example 8 The composite materials prepared in each embodiment and comparative example were used as active materials, mixed with conductive carbon black (SuperP) and binder (PVDF) at a mass ratio of 7:2:1, and N-methylpyrrolidone was added to grind into a uniform slurry. This slurry was coated onto a copper foil current collector, dried in a vacuum oven, and then stamped into circular electrodes. Using a lithium metal sheet as the counter electrode, a 1M LiPF6 carbonate solution as the electrolyte, and a polypropylene microporous membrane as the separator, a CR2032 type button half-cell was assembled in an argon-filled glove box. Electrochemical performance tests were conducted at room temperature, with a voltage test range of 0.005-3.0V (relative to Li). + / Li).

[0052] Test Example 9 This test example illustrates the effect of different vulcanization times on rate capability and cycle performance as follows: Figure 9 Example 2 demonstrates the rate performance of the composite materials prepared at different vulcanization times and commercial ZnO nanoparticles. After 10 cycles at 0.1C, followed by 5 cycles each at 0.2C, 0.5C, 1C, and 2C (1C = 1000 mA / g), ZnO / ZnS@C-4H exhibited the best rate performance, with average discharge capacities of 664.2, 324.4, 237.2, 146.9, and 96.1 mAh / g at 0.1C, 0.2C, 0.5C, 1C, and 2C, respectively. When the current density returned to 0.1C, the capacity recovered to 367.2 mAh / g. In contrast, the 2H sample had only 5.6 mAh / g at 2C, and the 6H sample had 72.9 mAh / g at 2C. All heterostructure samples outperformed commercial ZnO nanoparticles.

[0053] Figure 9 b demonstrates the stability after 100 cycles at a current density of 0.5C (all pre-activated 5 times at 0.1C); using the capacity after the second cycle as the standard for calculating capacity retention, ZnO / ZnS@C-4H has a discharge capacity of 171.8 mAh / g after 100 cycles, with a capacity retention (CR) as high as 69%, significantly higher than 2H (56%) and 6H (59%); commercial ZnO only retains 70.9 mAh / g under the same conditions, with a capacity retention of only 48%; 4 hours was identified as the optimal sulfidation time for preparing this heterostructure.

[0054] Test Case 10 This test example analyzes electrochemical impedance spectroscopy (EIS). Figure 10 a shows the EIS Nyquist curves of ZnO / ZnS@C-2H, 4H, and 6H before and after 100 cycles; the high-frequency to mid-frequency region shows two consecutive semicircles, while the low-frequency region shows a diagonal line. Figure 10The equivalent circuit of b is fitted, and the fitted resistance value is as follows: Figure 10 As shown in c; Roh is the solution and ohmic resistance, RSEI is the SEI film resistance, and Rct is the charge transfer resistance; all resistances increased after cycling, but the Rct value of ZnO / ZnS@C-4H was the lowest, at 193.4Ω, which is much lower than that of the 2H sample (274Ω) and the 6H sample (210.2Ω); the lower interfacial impedance confirms that the 4H sample has the best heterojunction synergistic effect, which is conducive to rapid electron / ion transport.

[0055] Test Example 11 This test case analyzes the cyclic voltammetry and charge-discharge performance as follows: Figure 11 a shows the first five CV curves of the ZnO / ZnS@C-4H composite electrode at scan rates of 0.005-3V and 0.2mV / s. In the first cathode scan, reduction peaks appear at approximately 0.6V and 0.5V, corresponding to the reduction of ZnO / ZnS to metallic zinc, the formation of Li2S / Li2O, and the formation of the SEI film. In the anodic scan, the broad peak at 0.3V-0.7V corresponds to the LiZn dealloying reaction, and the oxidation peak at 1.5V corresponds to the regeneration of ZnO / ZnS. Figure 11 b shows that the initial discharge capacity is 1114.7 mAh / g, the charging capacity is 586.2 mAh / g, and the coulombic efficiency is about 53%, which is due to the irreversible capacity loss caused by the formation of the SEI film. In subsequent cycles, the coulombic efficiency quickly stabilizes at >99%, indicating that the material has excellent reversibility.

[0056] Test Example 12 This test case illustrates the improvement in electrochemical performance after the introduction of rGO as follows: Figure 12 a demonstrates the rate performance after introducing rGO; the average discharge capacities of ZnO / ZnS@C@rGO at 0.1C, 0.2C, 0.5C, 1C, 2C, and 5C are 749.8, 623.7, 516, 394.6, and 265.1 mAh / g, respectively; when the current recovers to 0.1C, the capacity rebounds to 624 mAh / g; the corresponding charge-discharge curves are shown below. Figure 12 As shown in c; 100 cycles at a current density of 0.5C ( Figure 12 b) The initial discharge capacity of ZnO / ZnS@C@rGO reached 1044.6 mAh / g, and the coulombic efficiency was improved to 63.1%. After 100 cycles, the capacity was still maintained at 332.2 mAh / g, with a capacity retention rate of 67.3%, which is far superior to the unloaded rGO sample (171.8 mAh / g, CR=60.1%). Figure 12 The charge-discharge curves of d show that the voltage difference between the charge-discharge curves narrows significantly after the addition of rGO, indicating that the polarization effect is weakened.

[0057] Test Example 13 This test case illustrates the differential capacitance and overpotential analysis as follows: Figure 13 The differential capacity curves of the GO-modified and unmodified composite materials are shown; for example... Figure 13 As shown in Figure a, the second lithiation peak of the ZnO / ZnS@C composite electrode is at 0.93V. In subsequent cycles, this peak shifts to lower voltages, reaching 0.80V by the fifth cycle, corresponding to an overpotential of 0.13V. However, as... Figure 13 As shown in b, the overpotential of ZnO / ZnS@C@rGO after the introduction of rGO was significantly reduced to 0.06V; this result confirms the positive role of rGO in suppressing polarization during cycling and promoting reaction kinetics.

[0058] Test Example 14 This test example illustrates the comparison between heterostructures and single oxides as follows: Figure 14 The electrochemical performance of ZnO@C@rGO (Comparative Example 1) and ZnO / ZnS@C@rGO (Example 3) is compared; at all current densities, the reversible capacity of ZnO / ZnS@C@rGO is higher than that of ZnO@C@rGO; regarding cycling performance ( Figure 14 b) ZnO@C@rGO had a capacity of only 181.3 mAh / g after 100 cycles at 0.5C, with a capacity retention of only 55.3%; this indicates that heterostructure design is the key to achieving excellent electrochemical performance.

[0059] Test Example 15 This test example illustrates the electrochemical impedance and lithium-ion diffusion kinetics as follows: Figure 15 The synergistic mechanism between heterostructure and rGO was further explored; Figure 15 a and 15b show the EIS spectra and equivalent circuit fitting before and after the cycle; the fitting results (Table 2) show: The ZnO / ZnS@C@rGO heterostructure material exhibited a lower charge transfer resistance than ZnO@C@rGO both before and after cycling (426Ω vs. 531.8Ω before cycling; 18.58Ω vs. 38.66Ω after cycling); this indicates that the heterostructure significantly enhances the intrinsic kinetic properties of the material; based on the relationship between Z' and ω in the low-frequency region... - The linear relationship ¹ / ² (the slope is the Warburg coefficient σw) was calculated, and the σw ​​values ​​of ZnO / ZnS@C@rGO before and after cycling were 47.6 Ω·cm²·s. - ¹ and 30.2 Ω·cm²·s -¹, while the ZnO@C@rGO composite material exhibits higher values ​​(54.2 and 45.8); since the lithium-ion diffusion coefficient is inversely proportional to the Warburg coefficient, this proves that ZnO / ZnS@C@rGO has a faster lithium-ion diffusion capability.

[0060] In summary, this invention effectively solves the problems of poor conductivity and large cycling volume expansion of metal oxide anodes by constructing a two-dimensional nanosheet heterostructure composite material comprising a metal oxide phase, a metal sulfide phase, and an in-situ carbon phase. The in-situ carbon layer provides a buffer and conductive network, the two-dimensional nanosheets shorten the transport path, and the precisely controlled S / Zn molar ratio (e.g., 0.58) and the synergistic effect of the graphene substrate significantly reduce the interfacial charge transfer impedance and electrochemical overpotential (down to 0.06V) through the internal electric field. The above specific embodiments provide sufficient disclosure support for the core parameters and structural features defined in the claims through full-process illustration, detailed physical characterization, and electrochemical verification, and demonstrate excellent rate capability and cycling stability.

[0061] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No reference numerals in the claims should be construed as limiting the scope of the claims.

[0062] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A heterostructured composite material for lithium-ion batteries, characterized in that, It includes metal oxide phases, metal sulfide phases, and in-situ carbon phases; The metal oxide phase and the metal sulfide phase form a heterostructure, and the composite material exhibits a two-dimensional nanosheet morphology.

2. The heterogeneous composite material according to claim 1, characterized in that, The molar ratio R of sulfur to zinc in the composite material satisfies the following formula: R = n(S) / n(Zn) Wherein, n(S) is the amount of sulfur in the composite material, n(Zn) is the amount of zinc in the composite material, and 0.56≤R≤0.

81.

3. A method for preparing a heterogeneous composite material as described in claim 1 or 2, characterized in that, include: The metal-organic framework precursor and the sulfur source were subjected to thermal annealing under an inert atmosphere. The temperature T and heating rate v of the heat annealing process satisfy: T = 500℃, v = 2℃ / min.

4. The method according to claim 3, characterized in that, The metal-organic framework precursor is a two-dimensional zinc-1,3,5-benzenetricarboxylic acid (Zn-BTC) nanosheet, and the sulfur source is thioacetamide (TAA). The ratio of the mass m(TAA) of the sulfur source to the mass m(Zn-BTC) of the metal-organic framework precursor satisfies: m(TAA):m(Zn-BTC)=150:

68.

5. The method according to claim 3, characterized in that, Prior to the thermal annealing treatment, the method further includes a step of mixing graphene oxide with the metal-organic framework precursor. The ratio of the mass m(GO) of the graphene oxide to the mass m(Zn-BTC) of the metal-organic framework precursor satisfies: (GO):m(Zn-BTC)=5:

3.

6. The heterogeneous composite material according to claim 1, characterized in that, The composite material has a porous structure, with a BET specific surface area S_BET and a pore volume V. pore Satisfy S BET =126.39m² / g, V pore =0.41cm³ / g.

7. The heterogeneous composite material according to claim 1, characterized in that, The composite material is assembled from nanoparticles, and the grain size d of the nanoparticles satisfies: d≤5nm.

8. The heterogeneous composite material according to claim 1, characterized in that, The in-situ carbon phase is coated on the surface of the metal oxide phase and the metal sulfide phase, and the overpotential η of the composite material when used as the negative electrode of a lithium-ion battery satisfies: η≤0.06V.

9. The heterogeneous composite material according to claim 1, characterized in that, Under a discharge rate of 0.1C, the discharge capacity C of the composite material is... discharge Satisfy: C discharge ≥1044mAh / g.

10. The heterogeneous composite material according to claim 1, characterized in that, The composite material further includes a reduced graphene oxide substrate, and the two-dimensional nanosheet-shaped composite material is loaded on the reduced graphene oxide substrate; The discharge capacity C of the composite material at a rate of 5C 5C Satisfy: C 5C ≥265mAh / g; and the capacity retention rate CR of the composite material after 100 charge-discharge cycles at a current density of 0.5C satisfies the following formula: CR=(C 100 / C2)×100%; Among them, C 100 C1 represents the discharge capacity of the 100th cycle, C2 represents the discharge capacity of the 2nd cycle, and CR ≥ 67%.